Neonatal seizures and familial hypomagnesemia with secondary hypocalcemia - Pongsakdi Visudhiphan (2018)
This report describes two female siblings suffering from hypomagnesemia with secondary hypocalcemia, diagnosed at the third and fifth week of age. They both presented with recurrent generalized convulsions. Because their serum calcium levels were low at the early stage, the diagnosis of late-onset neonatal hypocalcemia was mistakenly made. Their seizures did not respond to parenteral calcium initially, but were completely terminated after the administration of magnesium. The possible cause of hypomagnesemia in these two patients was the selective defect of magnesium absorption in the small intestine. Both patients continued to receive daily supplement of magnesium orally to the last follow-up appointment at the ages of 23 and 12 years, respectively. Despite having several generalized seizures before the correct diagnosis and proper treatment, normal physical and mental development was achieved in both patients. © 2005 by Elsevier Inc. All rights reserved.